The Role of Village Websites in Increasing Community Participation: A Case Study of Batur Village, Semarang Regency - Adhi Susano; Meida Rachmawati (PT. Publikasiku Academic Solution, 2024)
This study aims to analyze the role of village websites in enhancing community participation in Batur Village, Getasan District, Semarang Regency. With a total population of 7,600, the research employed a simple random sampling method to select 100 respondents. Data were collected through a questionnaire that included questions regarding the level of access and use of the village website and participation in village activities. Data analysis was conducted using statistical tests, including Pearson Correlation Test and T-Test, to determine the relationship between website usage and community participation. The results showed a positive and significant relationship between the frequency of accessing the village website and the level of community participation, where respondents who actively used the website tended to be more involved in village activities, such as consultations and development programs. Comparative analysis also revealed significant differences between active users and non-active users of the website. Although the village website has significant potential to enhance participation, challenges such as a lack of community awareness and technological accessibility hinder its utilization. The study recommends that village officials be more proactive in educating the community about the importance of the website and providing relevant information to increase participation. Thus, the village website can serve as an effective means to enhance transparency and community engagement in the village development process.